Purchase Intention As A Mediator Of Price And Product Toward ‎Purchase Decision At Kedai Kopi Abah Sintang - Tia Kristiyani; Yasir Hudzaifah; Joko Susilo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research seeks to assess the influence of price and product on purchasing decisions, both directly and indirectly through purchase intention as a mediating variable. A quantitative method was employed, utilizing a survey technique. Data were gathered by distributing questionnaires to 100 respondents who are customers of Kedai Kopi Abah Sintang, and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (SmartPLS) approach. The results show that price has a significant and positive effect on both purchase intention and purchasing decisions, and also exerts an indirect influence on purchasing decisions through purchase intention. Conversely, the product factor does not have a significant impact on purchase intention or purchasing decisions, either directly or indirectly. Furthermore, purchase intention is found to have a significant effect on purchasing decisions. These findings highlight the crucial role of purchase intention in mediating the relationship between price and purchasing decisions, while it does not act as a mediator between product and purchasing decisions. This study is intended to serve as a useful reference for business practitioners in developing more effective marketing strategies, particularly in setting pricing strategies and enhancing consumer purchase intention.